Social Sector Expenditures and Rainy-Day Funds - Gonzalez, Christian Y.; Paqueo, Vicente B. (World Bank, Washington, DC, 2014)
Gonzalez and Paqueo examine the effects of budget stabilization funds--often called rainy-day funds--on the volatility of social spending and, for contrast, on nonsocial sector spending. They analyze the rainy-day funds of U.S. states. The authors find that rainy-day funds are ineffective in reducing the volatility of nonsocial sector expenditures but are effective in reducing the volatility of social sector expenditures. The authors also find that states that have stringent deposit and withdrawal rules have higher rainy-day fund balances, and thus are more effective in reducing the volatility of social sector expenditures. Finally, for long-term effectiveness, stabilization funds depend obviously on sustained economic growth.